Dural and Leptomeningeal Spine Metastases of Breast Cancer. (29th May 2019) - Matos, Fernando; Cerqueira, Luís
Abstract : We present a case of a 57-year-old female diagnosed with invasive ductal breast cancer, which was treated and in remission for 12 years. In 2018 she presented a progressive dorsal back pain, which prevented her from performing basic tasks. An MR study was performed and revealed the presence of an extramedullary metastatic sleeve located in the thoracic intradural space. Concomitant multiple small nodular foci were adhering diffusely to the spinal cord, compatible with leptomeningeal metastatic disease. The occurrence of both forms of spread in the spine is uncommon, and its distinction on imaging is of particular importance taking into account the differences in treatment approach and prognosis.